Effect of Different Water-Soluble Graphene: (Polystyrene Sulfonate, Titanate Coupling Agent and Glucose)/Reduced Graphene Oxide on the Performance of Magnesium-Air Batteries. Issue 2 (1st February 2022) - Ma, Jingling; Liu, Cuiran; Qin, Conghui; Jia, Xingliang; Zhang, Chenfei; Ren, Fengzhang; Wang, Guangxin
Abstract : Three kinds of water-soluble graphene: (WSG: polystyrene sulfonate, titanate coupling agent and glucose)/reduced graphene oxide were prepared for fabricating magnesium-air batteries with AP65 anode. Corrosion behaviour and discharge performance were investigated. The three kinds of water-soluble graphene added respectively in NaCl solution result in a more negative potential and a lower exchange current density in the potentiodynamic polarization curve of AP65 anode. The comprehensive discharge performance of the magnesium-air battery with the polystyrene sulfonate/reduced graphene oxide (PSS/RGO) is better than other 3 batteries. This is due to non-covalent adsorption of PSS on RGO and π − π interactions formed between PSS and RGO, which prevents graphene from agglomeration. PSS/RGO not only improves the ionic conductivity of solution, but also reduces the anode corrosion. Results of X-ray diffraction, fourier transform infrared spectrophotometer, scanning electron microscope and electrochemical impedance spectroscopy correlate well with the discharge and corrosion performance of AP65 anode in three water-soluble graphene solutions.